Manufactures Building construction, Alaska-Yukon-Pacific Exposition, Seattle, Washington, March 8, 1908 - Nowell, Frank H., 1864-1950 (1908)
On verso of photograph: Interior Mfg Bld. Mch 8. '08 Caption on image: x4 PH Coll 727.442 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number